2022
DOI: 10.3389/fphys.2022.981311
|View full text |Cite
|
Sign up to set email alerts
|

A potential role of p75NTR in the regulation of circadian rhythm and incremental growth lines during tooth development

Abstract: Objective: Tooth morphogenesis and the formation of hard tissues have been reported to be closely related to circadian rhythms. This study investigates the spatiotemporal expression and relationship of p75NTR with core clock genes, mineralization-related or odontogenesis-related genes, and aims to derive the potential role of p75NTR in regulating circadian rhythm and incrementality growth line formation during tooth development.Materials and methods: The dynamic morphology of the rat dental germ was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In odontoblasts, collagen synthetic and secretion activities showed a circadian rhythm, and collagen secreted during the day is twice the amount secreted at night, which is likely to control the circadian incremental lines of dentin ( Papakyrikos et al, 2020 ; Zheng et al, 2014 ) The clock proteins BMAL1, CLOCK, CRY1, PER1 and REV-ERBs are strongly expressed in odontoblasts, and the expression patterns are different in the crown and root dentin; the root is obviously strong ( Zheng et al, 2011 ; Fu et al, 2022 ). Bmal1 promotes cementoblast differentiation and cementum mineralization via Wnt/β-catenin signaling ( Yuan et al, 2022 ). Data obtained from in vivo studies of clock gene Bmal1 did not participate in the dentinogenesis process because the incremental lines persisted in both Bmal1 KO and wild-type mice housed in continuous darkness ( Kondratov et al, 2006 ).…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
“…In odontoblasts, collagen synthetic and secretion activities showed a circadian rhythm, and collagen secreted during the day is twice the amount secreted at night, which is likely to control the circadian incremental lines of dentin ( Papakyrikos et al, 2020 ; Zheng et al, 2014 ) The clock proteins BMAL1, CLOCK, CRY1, PER1 and REV-ERBs are strongly expressed in odontoblasts, and the expression patterns are different in the crown and root dentin; the root is obviously strong ( Zheng et al, 2011 ; Fu et al, 2022 ). Bmal1 promotes cementoblast differentiation and cementum mineralization via Wnt/β-catenin signaling ( Yuan et al, 2022 ). Data obtained from in vivo studies of clock gene Bmal1 did not participate in the dentinogenesis process because the incremental lines persisted in both Bmal1 KO and wild-type mice housed in continuous darkness ( Kondratov et al, 2006 ).…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
“…Moreover, several odontogenesis-related factors (e.g., ameloblastin, amelogenin, and lysosomeassociated membrane protein) have been reported to exhibit regular oscillating expression patterns in rat tooth germs at postnatal day 1 (PN1) 5,21,22 . In our previous studies 23 , the clock genes Bmal1, Clock, Per1, and Per2 were detected in both antenatal and postnatal tooth germs. Moreover, several mineralization-related and odontogenesis-related factors (e.g., runt-related transcription factor 2 (Runx2), alkaline phosphatase (ALP), collagen type I (Col1), distal-less homeobox 1 (Dlx1), Msh Homeobox 1 (Msx1), dentin sialophosphoprotein (Dspp), and dentin matrix acidic phosphoprotein 1 (DMP1)) were found to display similar oscillating expression patterns to the clock genes in ectomesenchymal stem cells (EMSCs) isolated from tooth germs.…”
Section: Introductionmentioning
confidence: 73%
“…These data con rm that tooth development, especially dental hard tissue formation, exhibits a characteristic circadian rhythm and is tightly controlled by clock genes. Interestingly, in our previous study, p75 neurotrophin receptor (p75NTR) was found to exhibit a close relationship with the circadian rhythm during tooth development 23,24 .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations